N1-methyladenosine (m1A) RNA modification: the key to ribosome control. (4th March 2020) - Shima, Hiroki; Igarashi, Kazuhiko
Abstract: RNA displays diverse functions in living cells. The presence of various chemical modifications of RNA mediated by enzymes is one of the factors that impart such functional diversity to RNA. Among more than 100 types of RNA modification, N 1 -methyladenosine (m 1 A) is found mainly in tRNA and rRNA of many living organisms and is known to be deeply implicated in the topology or function of the two classes of RNA. In this commentary article, we would like to deal with the functional significance of m 1 A in RNA, and also to describe one methyltransferase installing m 1 A in a large subunit rRNA, whose orthologue in Caenorhabditis elegans was discovered recently and was reported in this journal.